The Dead Sea Scrolls: Transmission of Traditions and Production of Texts. Edited by Sarianna Metso, Hindy Najman, and Eileen Schuller - Kooij, Arie van der (The journal of theological studies, 2014)
The volume under review contains the papers read at a conference in November 2009 in Toronto, in conjunction with the exhibit ‘Words that Changed the World’ held at the Royal Ontario Museum and co-sponsored by the Israel Antiquities Authority (p. xii). The focus is on the way traditions were transmitted and texts were produced in Early Judaism, as exemplified by the Dead Sea Scrolls., In his essay ‘Tradition and Innovation in the Dead Sea Scrolls’ (pp. 1–23) John J. Collins observes that the focus on the Law of Moses as reflected in Second Temple literature was in a sense much stronger and more detailed in writings after the Hellenistic reform and the Maccabean revolt than before.